EXPERIENCE IN RADON MITIGATION IN THE OPERATING BUILDINGS - A. V. Svetovidov; V. A. Venkov; G. A. Gorsky (Радиационная гигиена)
The article addresses results of measures of intensity reduction of radon intake to a dwelling from the bedrock and soil by the means of source isolation. It is noted that for mentioned type of radon mitigation a choice of membrane material and accuracy of isolation work are of the main importance. Authors demonstrate that it is practically impossible to get required attenuation factor of radon flow to the dwelling during implementation of radon mitigation in the limited part of building boundary. Two methods for evaluation of effectiveness of radon mitigation are described.